2014
DOI: 10.1007/s00277-014-2041-0
|View full text |Cite
|
Sign up to set email alerts
|

Older patients with chronic myeloid leukemia (≥65 years) profit more from higher imatinib doses than younger patients: a subanalysis of the randomized CML-Study IV

Abstract: The impact of imatinib dose on response rates and survival in older patients with chronic myeloid leukemia in chronic phase has not been studied well. We analyzed data from the German CML-Study IV, a randomized five-arm treatment optimization study in newly diagnosed BCR-ABL-positive chronic myeloid leukemia in chronic phase. Patients randomized to imatinib 400 mg/day (IM400) or imatinib 800 mg/day (IM800) and stratified according to age (≥65 years vs. <65 years) were compared regarding dose, response, adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…Nevertheless, Proetel et al showed that older patients (≥65 years) responded more slowly to standard dose imatinib (400 mg/day) than younger, but equally well to a higher dose (800 mg/day). Grade 3 and 4 adverse events were similar in both age groups [39]. Clinical implications of these findings are unclear, although the authors suggest that the optimal dose of imatinib for older patients may be higher than 400 mg/day.…”
Section: Survival Rates and Non-disease-related Prognostic Factorsmentioning
confidence: 69%
See 1 more Smart Citation
“…Nevertheless, Proetel et al showed that older patients (≥65 years) responded more slowly to standard dose imatinib (400 mg/day) than younger, but equally well to a higher dose (800 mg/day). Grade 3 and 4 adverse events were similar in both age groups [39]. Clinical implications of these findings are unclear, although the authors suggest that the optimal dose of imatinib for older patients may be higher than 400 mg/day.…”
Section: Survival Rates and Non-disease-related Prognostic Factorsmentioning
confidence: 69%
“…stage, Sokal, Hasford and EUTOS score, aberrant cytogenetics), which are beyond the scope of this overview, several nondisease-related factors might have an impact on the prognosis of CML. A number of studies indicate that, even after the introduction of imatinib in 2001-2002, elderly CML patients (>60-70 years) have an inferior survival than younger ones [28,[36][37][38], although recent reports from UK and the German CML Study IV concluded that the relative survival was almost identical for patients under and over 60 (65)years [9,39]. Possibly, the underuse of imatinib (or other TKIs) in the elderly CML patient populations during the first years after its introduction explains the inferior results in the very elderly population as reported in some population-based studies [8].…”
Section: Survival Rates and Non-disease-related Prognostic Factorsmentioning
confidence: 97%
“…With the advent of first TKI, namely imatinib, also elderly patients, usually candidate to palliative approach, have been treated and cured [1]. A 5-year relative survival of elderly CML patients (≥65 years) was shown to be comparable to that of younger patients [2]. As recent data from large population-based registries report a median age at diagnosis of 56 years [3], it is reasonable to consider that many of the CML patients currently under treatment have even a greater median age.…”
Section: Introductionmentioning
confidence: 99%
“…79 A subset analysis from this randomized study also showed a greater benefit for patients over 65 years of age. 80 Another recent randomized intergroup phase II study also demonstrated deeper molecular responses in the 800 mg daily arm compared with 400 mg daily, with MR 4 of 25% and 10%, respectively, with a trend for improved progression-free and overall survival, but with substantially more grade 3 and 4 side-effects. 81 There is also some evidence that imatinib 600 mg daily is tolerated in more than 80% of CML patients and results in superior cytogenetic and molecular responses at 12 and 24 months compared to the conventional 400 mg daily dose.…”
mentioning
confidence: 99%